Comparative evaluation of classical inferior alveolar nerve block and gow-gates nerve block for surgical removal of mandibular third molar: A prospective study - Abhilash Mathews Thomas (Wolters Kluwer Medknow Publications, 2021)
Background: The most commonly used nerve block procedure to anesthetize the mandibular arch is the classical inferior alveolar nerve block (IANB). In 1973, Gow-Gates developed a new procedure known as the Gow Gates nerve block, to achieve anesthesia in the same area with fewer complications. Methodology: The study comprised 80 patients who reported for the surgical removal of impacted third molar. The patients were randomly assigned into two groups– Group I received Gow-gates nerve block and Group II were administered classical IANB. Positive aspiration, meantime for the onset of anesthesia, mouth opening before and after each block and pain during the surgical procedure were compared. Results: Group 1 yielded positive aspiration in 2.5% of the cases (one patient) and 15% had positive aspiration in Group 2 (six patient). The mean time taken for onset of anesthesia was 6.16 min in Group 1 as compared to 2.78 min in Group 2. While comparing the quality of anesthesia between the blocks, 87.5% of the patients in Group 1 and Group 2 had successful anesthesia equally i.e., 35 of the 40 patients fell into category 1 and 2 of the eight-point category rating scale in both the groups and the remaining five patients (12.5%) in both the groups had unsuccessful anesthesia. Conclusion: Both approaches offer quality anesthesia in the posterior mandibular area when meticulously followed. The percentage of unsuccessful anesthesia in the Gow-Gates group could be attributed to the inexperience of the operator. Postoperative comfort and patient satisfaction were greater in the other group.